Enterprise content management platform Web services based on CXF framework - Bin HOU; Hongbing TU; Yunfu WANG (Dianxin kexue)
After comparing and analyzing the main business and implementation plan for an enterprise content management platform web service,a technical scheme was put forward,which was using a table interface combined with the CXF framework,taking both responsiveness and stability requirements for web services into account,while also facilitating configuration adjustments due to the frequent change of business requirements.On the basis of that,a web service configuration module was developed to enhance the web service's scalability.